2021
DOI: 10.1111/1365-2664.14049
|View full text |Cite|
|
Sign up to set email alerts
|

Movement of forest‐dependent dung beetles through riparian buffers in Bornean oil palm plantations

Abstract: 1. Fragmentation of tropical forests is increasing globally, with negative impacts for biodiversity. In Southeast Asia, expansion of oil palm agriculture has caused widespread deforestation, forest degradation and fragmentation.2. Persistence of forest-dependent species within these fragmented landscapes is likely to depend on the capacity of individuals to move between forest patches. In oil palm landscapes, riparian buffers along streams and rivers are potential movement corridors, but their use by moving an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Changes in the demographic parameters associated with environmental conditions have also been found to be related to dispersal and the differential mortality of the sexes, with the prediction that the ASR in better quality habitats will be biased toward the sex with a lower capacity for movement and a lower probability of death ( Julliard 2000 ). In our study, movement was different between species and was related to differential habitat use and their resource exploration ability, as expected for species with opposite sets of ecological traits ( Cultid-Medina et al 2015 ; Silva and Hernández 2015 ; Gray et al 2021 ). In this sense, our results—supported by the greater rate of recapture, number of trajectories, and distance covered within the forest—show that female D .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Changes in the demographic parameters associated with environmental conditions have also been found to be related to dispersal and the differential mortality of the sexes, with the prediction that the ASR in better quality habitats will be biased toward the sex with a lower capacity for movement and a lower probability of death ( Julliard 2000 ). In our study, movement was different between species and was related to differential habitat use and their resource exploration ability, as expected for species with opposite sets of ecological traits ( Cultid-Medina et al 2015 ; Silva and Hernández 2015 ; Gray et al 2021 ). In this sense, our results—supported by the greater rate of recapture, number of trajectories, and distance covered within the forest—show that female D .…”
Section: Discussionsupporting
confidence: 74%
“…It is known that repeated sampling of marked individuals produces reliable estimates of many population parameters, and Ancona et al (2017) point out that capture–recapture is one of the most appropriate methods for estimating sex ratio under natural conditions. Compared with other studies on dung beetles at the population level ( Escobar and Chacón de Ulloa 2000 ; Escobar 2003 ; Arellano et al 2008 ; Silva and Hernández 2015 ; Gray et al 2021 ), we recorded a high recapture rate (6–15%) and this allowed us to reliably describe the variation in ASR as well as the aggregation of males and movement patterns for both species. Although biases in catchability and the probability of detection due to physiological state and behavioral differences between the sexes has been found in several taxa ( Dénes et al 2015 ), in dung beetles, there is no sufficient evidence that baited traps attract one sex more than the another.…”
Section: Discussionmentioning
confidence: 51%
“…Traps were set in the morning and left for 48 h before collection (for further details, see refs. 36,[54][55][56] ).…”
Section: Study Landscapementioning
confidence: 99%
“…Similar, Villemey et al (2018) reported that linear transportation infrastructure verges constitute a habitat and/or a corridor for insects [32]. Gray et al (2022) indicated recently that the important use of riparian buffers in oil palm plantations for forestdependent dung beetle species [33]. Furtherly, fauna could even adapt to alternation of landscape corresponds to the fluctuation of the flood [34].…”
Section: Effects Of Urbanization On River Corridormentioning
confidence: 87%